2013
DOI: 10.1007/s00284-013-0412-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Effects of Broad-Spectrum Antibiotics and Biosurfactants on Established Bacterial Biofilms

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science +Business Media New York. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 46 publications
0
41
2
Order By: Relevance
“…A recent report found no anti-biofilm activity of chloramphenicol against Staphylococcus aureus , E. coli , and Micrococcus luteus . Importantly, the authors only used a concentration of only 0.005 mg/ml, a concentration well below the planktonic MIC for our bacterium and only slightly higher than the MICs for their three isolates (maximum 0.0031 mg/ml) [28]. In contrast, our study shows that high doses (0.08 and 0.80 mg/ml) of chloramphenicol reduce the mass of preformed S. marcescens biofilms, and the 0.80 mg/ml concentration decreases the viability of biofilms compared with untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report found no anti-biofilm activity of chloramphenicol against Staphylococcus aureus , E. coli , and Micrococcus luteus . Importantly, the authors only used a concentration of only 0.005 mg/ml, a concentration well below the planktonic MIC for our bacterium and only slightly higher than the MICs for their three isolates (maximum 0.0031 mg/ml) [28]. In contrast, our study shows that high doses (0.08 and 0.80 mg/ml) of chloramphenicol reduce the mass of preformed S. marcescens biofilms, and the 0.80 mg/ml concentration decreases the viability of biofilms compared with untreated controls.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates stored at Ϫ80°C were grown on LB agar and incubated at 37°C. A single colony was selected and placed into 3 ml of LB (10 [31]) were also included.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that they are able to alter a substrate's surface energy (Busscher and van der Mei 1997) and increase surface area (Rodrigues et al 2006), which would make biosurfactants important potential candidates for oral health-related applications. A direct application of the latter properties is adjuvant delivery of antibiotics using biosurfactants, resulting in a reduced therapeutic dosage of antibiotics (Quinn et al 2013). In this context, sophorolipids demonstrated potency when delivered in a pharmaceutical formulation where they acted synergistically with antibiotics such as Tetracycline and Cefaclor showing an increase in the permeability of the antibiotics across the outer membrane of the bacteria (Joshi-Navare and Prabhune 2013).…”
Section: Potential Biosurfactant Applications For Oral Health and Hygmentioning
confidence: 99%